Combined traffic control of irrigation on heterogeneous field - Szabó, Andrea; Juhász , Csaba; Gálya Farkasné , Bernadett; Kövesdi , Ádám; Tamás , János; Nagy , Attila (Acta Agraria Debreceniensis, 2022)
In arid areas, such as Hungary, most climate models forecast a rise in water scarcity. Irrigated land accounts for 2% of agricultural land in Hungary, with most irrigation technology being relatively outdated. The aim of this research was to lay the foundation for a combined traffic management system for a water-saving precision irrigation system on an 85-ha field in the Tisza River basin’s reference region. High-precision soil maps were created to support the water-efficient variable-rate irrigation system by selecting and selecting areas for different agrotechnical implementations and precision farming zones.